Awareness of Glaucoma in Different Groups of Urban Population - Asif Manzoor, Nasira Inayat, Muhammad Moin (Pakistan Journal of Ophthalmology, 2014)
Purpose: To evaluate the level of glaucoma awareness among different groups of urban population Material and Methods: A survey was conducted by Ophthalmology unit-II, Ameer-ud-Din Medical College / Post Graduate Medical Institute / Lahore General Hospital, Lahore; Pakistan. Survey was conducted in three different groups of civilians using non probability, purposive sampling. Group I consisted of 150 Medical Students of first and second year in their MBBS; Group II comprised of 115 student nurses; and Group III was composed of 150 adults from all public sectors. This study is an observational and cross sectional study. Results: A total of 415 adults answered the questionnaire made for awareness of glaucoma. In Group I, 13.3% stated that they did not know what glaucoma meant. All in group II answered as to what glaucoma meant; whereas, 48.7% in group III had not heard about glaucoma. In Group I, 36% said that it was raised intra ocular pressure, 21.3% said it was an eye disease, 16.7% thought that it was another name for blindness, 8% wisely answered it as an optic neuropathy, 2.3% translated the word glaucoma in their local language (Urdu) as ‘kalamotia’, 1.3% students thought that it was a glucose related disorder, or a form of diabetes and 0.7% thought that it was a name given to blindness due to diabetes mellitus. In Group II, 80.9% nurses stated that the term ‘glaucoma’ meant a raised intraocular pressure, 15.7% thought that glaucoma meant blindness, 2.6% stated that it was an optic neuropathy and 0.9% wrote that glaucoma meant headache and vomiting. In Group III, 24% participants said glaucoma meant loss of vision, 22% stated it was an eye disease, 4.7% knew that it was due to raised intraocular pressure, and 0.7% said that glaucoma meant watering from the eye. Conclusion: The awareness of glaucoma is low in the general public. An efficient information, education and communication strategy needs to be designed for early detection and treatment of glaucoma to prevent blindness. Key words: Glaucoma, blindness, intraocular pressure.